HCC biomarkers – state of the old and outlook to future promising biomarkers and their potential in everyday clinical practice - Schlosser, Sophie; Tümen, Deniz; Volz, Barbara; Neumeyer, Katja; Egler, Niklas; Kunst, Claudia; Tews, Hauke Christian; Schmid, Stephan; Kandulski, Arne; Müller, Martina; Gülow, Karsten (Frontiers in Oncology, 2022)
Hepatocellular carcinoma (HCC) is one of the most common and deadly tumors worldwide. Management of HCC depends on reliable biomarkers for screening, diagnosis and monitoring of the disease as well as predicting response towards therapy and safety. To date, imaging has been the established standard technique in the diagnosis and follow up of HCC. However, imaging techniques have limitations, especially in the early detection of HCC. Therefore, there is an urgent need for reliable, non/minimal invasive biomarkers. To date, alpha-fetoprotein (AFP) is the only serum biomarker used in clinical practice for the management of HCC. However, AFP is of rather low quality in terms of specificity and sensitivity. Liquid biopsies as a source for bi have become the focus of clinical research. Our review highlights alternative biomarkers derived from liquid biopsies, including circulating tumor cells, proteins, circulating nucleic acids and exosomes and their potential for clinical application. The use of defined combinations of different biomarkers will open new perspectives for diagnosing, treating and monitoring HCC.